A decision-making method for choosing concrete forming systems. Issue 1 (2nd January 2018) - Safa, Mahdi; Reinsma, Sean; Haas, Carl T.; Goodrum, Paul M.; Caldas, Carlos H.
Abstract : In recent decades, advances in formwork systems, which represent an essential component of any concrete placement, have paralleled significant improvements in concrete technology. While valuable information about the design of a particular formwork system is readily available, little guidance exists with respect to methods of choosing an appropriate forming system for a specific application. This paper describes applications of the main types of formwork systems and provides details about alternative formwork systems. This study mainly contributes to the development of previously unavailable model for facilitating and validating formwork decisions. A variety of project examples were considered based on field data and information provided by industrial partners. In particular, the emerging predominance of insulated concrete formwork for mid-rise residential structures is examined. The developed system can be used as a high-level decision support tool for the selection of forming systems.